2012
DOI: 10.1097/inf.0b013e31825c124a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cotrimoxazole Prophylactic Treatment on Adverse Health Outcomes Among HIV-exposed, Uninfected Infants

Abstract: Background The World Health Organization guidelines recommend cotrimoxazole prophylactic treatment (CPT) for all HIV-exposed infants from age 6 weeks to the cessation of breastfeeding and the exclusion of HIV infection. There are limited data about the effects of CPT among this population of infants. We examined the effects of CPT on adverse health outcomes among HIV-exposed infants during the first 36 weeks of life by using data from the Breastfeeding, Antiretrovirals, and Nutrition (BAN) study, a large clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Infants randomized to ARV received daily oral nevirapine (details previously reported 17 . Starting on June 13, 2006, cotrimoxazole prophylaxis (CPT) (240 mg once daily) was provided to all infants >6 weeks old and initiated for all mothers with a CD4<500 cells/uL in pregnancy; 23 in this report 68% and 43% of infants and mothers received CPT, respectively. In March 2008, the data safety monitoring board at the National Institute of Allergy and Infectious Diseases reviewed data from the enrolled 1857 mother-infant pairs and observed that HIV transmission through breast milk was higher in the no-drug study arms.…”
Section: Methodsmentioning
confidence: 99%
“…Infants randomized to ARV received daily oral nevirapine (details previously reported 17 . Starting on June 13, 2006, cotrimoxazole prophylaxis (CPT) (240 mg once daily) was provided to all infants >6 weeks old and initiated for all mothers with a CD4<500 cells/uL in pregnancy; 23 in this report 68% and 43% of infants and mothers received CPT, respectively. In March 2008, the data safety monitoring board at the National Institute of Allergy and Infectious Diseases reviewed data from the enrolled 1857 mother-infant pairs and observed that HIV transmission through breast milk was higher in the no-drug study arms.…”
Section: Methodsmentioning
confidence: 99%
“…In total 1692 HIV‐exposed, 2800 HIV‐uninfected and 1486 HIV‐infected children aged between 6 weeks (Dow et al . ) and 15 years (Thera et al . ) were included in the meta‐analyses.…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
“…The only exception was the study by Dow et al . (), which compared the incidence of malaria between HIV‐exposed children before and after 2006, the year CPT guidelines were introduced in Malawi. All studies adjusted for potential confounders at the analysis stage; however, the variables included in the multivariable models differed across studies (Appendix 3).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…However, other than temporary protection from malaria, CPT offered no protection against anemia, malnutrition or severe illness and death for HIV negative children. [16,17] Given limited data that CPT may increase risk of diarrheal illness in HIV uninfected infants there is a need to define the optimal duration of cotrimoxazole prophylaxis and possibly reexamine current guidelines. [18]…”
Section: Long-term Impact Of Hiv Exposure On Infant and Childhoodmentioning
confidence: 99%